Incorporation of [2H1]-(1R, 2R)- and [2H1]-(1S, 2R)-glycerols into the antibiotic nucleocidin in Streptomyces calvus. Issue 38 (18th September 2017) - Feng, Xuan; Al Maharik, Nawaf; Bartholomé, Axel; Janso, Jeffrey E.; Reilly, Usa; O'Hagan, David
Abstract : Both pro-R hydroxylmethyl hydrogens of glycerol are incorporated into nucleocidin in Streptomyces calvus . Abstract : Deuterium incorporations from [ 2 H1 ]-(1 R, 2 R ) and [ 2 H1 ]-(1 S, 2 R ) glycerols into the fluorine containing antibiotic nucleocidin, in Streptomyces calvus indicate that one deuterium atom is incorporated at the C-5′ site of nucleocidin from each of these isotopomers of glycerol. Two deuteriums become incorporated at C-5′ of nucleocidin after a feeding experiment with [ 2 H5 ]-glycerol. These observations indicate that there is no obligate oxidation of the pro-R hydroxymethyl group of glycerol as it progresses through the pentose phosphate pathway and becomes incorporated into the fluorinated antibiotic.